Aplikasi Sistem Pendukung Keputusan Pemilihan Supplier Obat Menggunakan Metode Elimination Et Choix Traduisant La Realite (ELECTRE) - Ardean Raflian; Tiwuk Widiastuti; Meiton Boru (J-ICON : Jurnal Komputer dan Informatika, 2022)
Pharmacies are decisive places in providing, distributing, and dispensing drugs need by the community. The high demand for drugs at the Crystal Farma Pharmacy Oebobo makes it difficult for pharmacists to choose more than one drug supplier. This study aims to build a decision support system for drug supplier selection. This system provides results in the form of recommendations for the best suppliers, which are taken into consideration by pharmacy managers. Application elimination et choix radiant la reality (ELECTR) method, using the criteria of price, discount, expiration date, stock, distance, and payment system for four drug suppliers. ELECTRE method resulted in the drug rating of Amoxicillin 500 Mg, namely PT. Indofarma Global Medika and PT. Enseval Putera Megatrading. In an experiment testing the calculation on the system using case data on as many as four types of generic drugs, namely Allopurnol, Amlodipine, Mefenamic Acid, and Paracetamol, the results of PT. Sapta Sari Tama a recommended for drugs Allopurinol and Amlodipine. At PT. Kimia Farma Trading & Distribution a recommended for Mefenamic Acid and PT. Marga Nusantara Jaya is recommended for Paracetamol medicine. In black-box testing, getting the results of the overall functional percentage of the system using nine testing techniques is 100% successful. In user acceptance testing (UAT) testing, the user satisfaction level of the questionnaire method is 94% of the total respondents, four people and two pharmacies, namely Apotek Crystal Farma Oebobo and Apotek Crystal Farma Kuanino